Abuso sexual temprano y la salud mental en la vida adulta. - Paredes Garzón, Ariana Pamela (2024)
Early ages are determinant in the development of human beings, where the foundations of mental health are established throughout life. At present, childhood, and adolescence are affected by an insidious phenomenon: sexual abuse, which crosses geographical, cultural, and socioeconomic boundaries, leaving deep scars that, although not visible in the short term, have a lasting impact on mental health that is exacerbated in adulthood of the victims, many of them with irreversible sequelae, becoming a severe public health problem.The present research, quantitative, bibliographic, descriptive, and cross-sectional, aims to analyze early sexual abuse and mental health in adulthood; it was based on the review and analysis of scientific documents from indexed databases such as Scopus, ProQuest, Scielo, Redalyc, Science Direct. PubMed, Dialnet, using a sample of 42 articles from the last 10 years, which were methodologically validated using the matrix of the Critical Review Form for Quantitative Studies (CRF-QS). The results showed a higher prevalence in females between the ages of 10 and 17 years; socioeconomic, family, and demographic risk factors, such as low income, presence of stepfathers or single mothers, and residence in urban areas. Most of the aggressors are men, often relatives or close relatives, the abuse occurs mainly at home with a prevalence of touching and penetration (higher in adolescents), there is no health care seeking and there is a low rate of reporting, predominantly in women; the immediate consequences include early motherhood and sexually transmitted infections. Similarly, several persistent conditions were found in the mental health of adults, among the most frequent: depression, anxiety, post-traumatic stress disorder, obsessivecompulsive disorder, borderline personality disorder, self-harm, substance abuse, suicide attempts, conflictive relationships, delinquency, interpersonal and sexual difficulties, emotional distress, attention deficit, psychosocial dysfunction, revictimization and tendency to have a victimized child; unfavorable socioeconomic contexts represent precipitating factors.